The Modernization of Educational Process in the Information and Computer Space - Iryna Soina; Nina Petrusenko (Pedagogical Discourse, 2017)
This article analyzes the application of information technology in the formation of the virtual educational space. New methods such as digital writing and visual rhetoric are studied. The role of the Internet in the modern information and computer space as a result of the use of blogs, podcasts and wiki resources, as well as the development of distance courses, in particular, language are examined. The modern possibilities of multimedia and information technology in order to promote the intensification and the efficiency of the educational process are analyzed. Methodical and technological value of the computer and multimedia content, which are interactive animations in the process of learning a foreign language are studied. The media’s role in the educational process, taking into account the individual, intellectual and cognitive abilities of each student and appropriate differentiation of the amount of educational material are analyzed. This article analyzes the multimedia English course «English Discoveries». Introduction in educational process of innovative approach allows to carry out purposeful formation of creative and critical thinking, experiential teaching and research skills, to learn best practices and implementing it in practice. To ensure the quality of the educational process multimedia learning should become an integral component of modern methodical system. World experience of use of modern digital technologies and multimedia devices in the methodological centers and schools shows that their active use in training activities increases the efficiency of the educational process, creates a condition for individual and differentiated instruction of students, increases the time for speaking practice for each, provides high motivation to learn, helps to overcome personal psychological barrier of communication.